ANALISIS PENGARUH PERIKLANAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI EKUITAS MEREK SEBAGAI VARIABEL INTERVENING PADA PRODUK NESCAFE DI KOTA SEMARANG - Primatika, Roza Azizah; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2018)
The purpose of this study to analyze Advertising and Sales Promotion on Brand Equity  and  the  impact  on  Purchase  Decision.  The  population  of  the  study  was  all consumers  who  had  ever  done  purchase  transaction  on  Nescafe  product,  where respondents are Semarang people. The samples in this study were 120 respondents. The method of collecting data through questionnaires. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 22.0 as the analysis instrument.The result show that the Advertising has a positive and significant effect on Brand Equity, Sales Promotion has a positive and significant effect on Brand Equity, Advertising has a positive and significant effect on Purchase Decision, Sales Promotion has a negative impact on Purchase Decision, and Brand Equity has a positive and significant effect on Purchase Decision.